Microstructural characterization of hematite during wet and dry millings using Rietveld and XRD line profile analyses - Peukert, Wolfgang; Pourghahramani, Parviz; Altin, Ergün; Mallembakam, Madhusudhan Rao; Forssberg, Eric (Powder Technology, 2008)
The effects of extended milling in a stirred media mill and a tumbling mill on the structural changes in hematite have been examined using a combination of particle size analysis, BET surface areas, X-ray diffraction (XRD), thermal (TG and DSC) and FTIR measurements. Rietveld's whole profile fitting based on crystal structure refinement and the Warren-Averbach's method of X-ray line profile analysis were applied to monitor the microstructural evolution of the hematite phase. It is found that the BET surface area, X-ray amorphization phase content and XRD line breadths increase over the specific energy input. The use of stirred media mill exhibits larger surface areas, smaller particle sizes, more XRD line broadening and subsequently greater structural distortions compared to the tumbling mill for a given energy input; although the X-ray amorphous phase content remains unaffected by the grinding environments. The maximum X-ray amorphization degree of about 80 and 95% were calculated at a specific energy of 22,400 and 82,000 kJ/kg in the tumbling and stirred media mills respectively. The maximum specific BET surface area in the stirred media and tumbling milling increases to about 72.5 and 6.8 m/g after 82,000 and 22,400 kJ/kg energy consumption respectively. As a result of structural refinement during milling, the surface-weighted crystallite size in ground hematite are 17 and 4 nm after consuming 22,400 and 82,000 kJ/kg in the tumbling and stirred media mills respectively, corresponding to the volume-weighted crystallite size of 17 and 11 nm. For the same energy consumption in the mills, in turn, the root mean square strain, 〈 ε 〉, increases to about 4.4 × 10 and 4.9 × 10. The results of the two applied methods are compared and discussed in details. In addition, thermogravimetric analysis of the wet ground samples reveals that the TG curves represent two weight loss steps. A weight loss is observed around 100 °C in the sample which is attributed to the removal of adsorbed water due to the wet milling operations. A strong weight loss step starting from 100 to 400 °C is attributed to surface/bulk dehydroxilation of iron hydroxides. The weight loss increases with extending of the milling. In contrast, the dry milled samples yield negligible weight losses comparing with the wet ground samples. © 2007 Elsevier B.V. All rights reserved.
Keywords: Iron oxide; Mechanical activation; Structural changes; Wet and dry milling